Susceptibility of Candida albicans from cystic fibrosis patients - Sabino, Raquel (2017)
Candida albicans is a common microbe, colonizer and potential pathogen found in respiratory cultures of cystic fibrosis (CF) patients. Because of possible development of resistance in patient isolates resulting from residence in the abnormal milieu of CF patient airways, or from exposure to antifungals, and considering the possibility of patient-to-patient spread of microbes and reports of elevated resistance to other fungal pathogens, it was important to assay the susceptibility of isolates of Candida and compare that profile to isolates from the community. In our center, and unlike another fungal pathogen, no increase in resistance of Candida isolates of the CF cohort was found.